1988
DOI: 10.4319/lo.1988.33.4.0528
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of urea C and urea N by the coastal marine diatom Thalassiosira pseudonana

Abstract: Urea uptake rates of Thalassiusiru pseudonana (clone 3H) were determined using [14C]urea,[15N]urea, and by measuring disappearance of dissolved urea from the medium after adding 10 lg-atoms urea-N liter-'. In nitrate-sufficient cultures, the average [14C]urea uptake rate was 60% of the urea disappearance rate. Nitrate uptake continued in the presence of urea at a reduced rate, and only 15% of the urea N taken up was retained by the phytoplankton.The increase in PON during incubation was roughly equal to the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
2
34
2
2
Order By: Relevance
“…4). These results are comparable with those of Lund & Blackburn (1989), who measured production of 14 C-DIC after addition of 14 C-urea to a coastal marine sediment but no incorporation of 14 C. Release of 13 C-or 14 C-DIC following addition of 13 C-or 14 C-urea was also observed for algal cultures (Price & Harrison 1988, Antia et al 1991 and references therein), bacteria from estuarine waters (Jørgensen 2006) and a natural planktonic microbial community (Tamminen & Irmisch 1996). Moreover, uncoupled uptake of 15 N and 13 C from dual-labeled urea has been reported for coastal waters (Mulholland et al 2004, Fan & Glibert 2005, Andersson et al 2006.…”
Section: N Versus 13 C: Ureasupporting
confidence: 79%
See 2 more Smart Citations
“…4). These results are comparable with those of Lund & Blackburn (1989), who measured production of 14 C-DIC after addition of 14 C-urea to a coastal marine sediment but no incorporation of 14 C. Release of 13 C-or 14 C-DIC following addition of 13 C-or 14 C-urea was also observed for algal cultures (Price & Harrison 1988, Antia et al 1991 and references therein), bacteria from estuarine waters (Jørgensen 2006) and a natural planktonic microbial community (Tamminen & Irmisch 1996). Moreover, uncoupled uptake of 15 N and 13 C from dual-labeled urea has been reported for coastal waters (Mulholland et al 2004, Fan & Glibert 2005, Andersson et al 2006.…”
Section: N Versus 13 C: Ureasupporting
confidence: 79%
“…In order for bacteria and algae to use urea as a nitrogen source for growth, urea first needs to be broken down to NH 4 + and DIC. Subsequently, the resulting NH 4 + can be used to synthesize amino acids for production of proteinaceous biomass, while the DIC may be used as a carbon source for photosynthesis (Price & Harrison 1988, Antia et al 1991. This urea metabolization pathway appears to be widespread because urease, the enzyme responsible for the breakdown of urea, is a common enzyme used by algae as well as bacteria (Price & Harrison 1988, Mobley & Hausinger 1989, Antia et al 1991, Zehr & Ward 2002.…”
Section: N Versus 13 C: Ureamentioning
confidence: 99%
See 1 more Smart Citation
“…The organic nitrogen compound, urea, has long been recognized as an important nitrogen source for primary producers in marine environments (Remsen 1971, Eppley et al 1973, McCarthy et al 1977, Harrison et al 1985, Sorensson & Sahlsten 1987, Price & Harrison 1988, Antia et al 1991, Cochlan & Harrison 1991. Urea is excreted as an endproduct of nitrogen metabolism by a variety of marine invertebrates (Wright 1975, Regnault 1987, Boucher & BoucherRodoni 1988, Stickle 1988, Lomstein et al 1989 including zooplankton (Eppley et al 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, urea uptake rates in the western Sargasso Sea have been estimated to be near the maximum potential (Price and Harrison 1988a) and dual stable isotope ( 14 C-and 15 N-urea) labeling experiments in the Arctic Ocean show that urea-carbon is respired as CO 2 , while most of the urea-nitrogen is incorporated by phytoplankton (Harrison et al 1985). Culture experiments with the diatom Thalassiosira pseudonana revealed that significant portions of urea-nitrogen taken up may be released back to the environment as ammonia followed by rapid reabsorption (Price and Harrison 1988b). In both coastal and open ocean regimes urea uptake typically accounts for a third of the total nitrogen uptake (McCarthy 1972;Price and Harrison 1988a).…”
Section: ) Concentrationsmentioning
confidence: 99%